Lipid-lowering treatment patterns among patients with type 2 diabetes mellitus with high cardiovascular disease risk - Quek, Ruben G W (BMJ Open Diabetes Res Care, 2015)
OBJECTIVE: To examine real-world treatment patterns of lipid-lowering treatment and their possible associated intolerance and/or ineffectiveness among patients with type 2 diabetes mellitus initiating statins and/or ezetimibe. RESEARCH DESIGN AND METHODS: Adult (aged ≥18 years) patients diagnosed with type 2 diabetes who initiated statins and/or ezetimibe from January 1, 2007 to June 30, 2011 were retrospectively identified from the IMS LifeLink Pharmetrics Plus commercial claims database. Patients were further classified into 3 high-risk cohorts: (1) history of cardiovascular event (CVE); (2) two risk factors (age and hypertension); (3) aged ≥40 years. Patients had continuous health plan enrolment ≥1 year preindex and postindex date (statin and/or ezetimibe initiation date). Primary outcomes were index statin intensity, treatment modification(s), possible associated statin/non-statin intolerance and/or ineffectiveness issues (based on treatment modification type), and time-to-treatment modification(s). Analyses for each cohort were stratified by age groups (<65 and ≥65 years). RESULTS: A total of 9823 (history of CVE), 62 049 (2 risk factors), and 128 691 (aged ≥40 years) patients were included. Among patients aged <65 years, 81.4% and 51.8% of those with history of CVE, 75.6% and 44.4% of those with 2 risk factors, and 77.9% and 47.1% of those aged ≥40 years had ≥1 and 2 treatment modification(s), respectively. Among all patients, 23.2–28.4% had possible statin intolerance and/or ineffectiveness issues after accounting for second treatment modification (if any). CONCLUSIONS: Among patients with type 2 diabetes with high cardiovascular disease risk, index statin treatment modifications that potentially imply possible statin intolerance and/or ineffectiveness were frequent.